Overview of Public Health Laboratory Readiness in Primary Health Care in Indonesia: A Scoping Review - Imanul Abdi; Sutopo Patria Jati; Antono Surjoputro (GLOBAL HEALTH SCIENCE GROUP, 2025)
This study examines the readiness of public health laboratories in Indonesia's primary healthcare services, focusing on resource distribution, critical result reporting, and health policy implementation. A review of several studies reveals that laboratory readiness is limited by facility constraints, drug availability, and healthcare workers' understanding of critical result handling. Policies like BLUD and lean hospital approaches can enhance operational flexibility in laboratories. Recommendations are directed toward strengthening resource distribution and staff training to improve laboratory service quality in primary healthcare.